Student Performance Analysis Using Artificial Intelligent Method - M. M., Noor; K., Kadirgama; M. S. M., Sani; M. R. M., Rejab; M. M., Rahman; M. Y., Taib (2009)
Measuring of academic performance of students is challenging since student performance is product of socio-economic, psychological and environmental factors. This paper discussed the neural network method were used to measure student performance in Thermodynamic at Faculty of Mechanical Engineering, University Malaysia Pahang (UMP). Randomly 65 mechanical engineering students were picked to analysis their performance in these subjects with 5 variables which are Test1, Test 2, Final Examination, assignment and Quizzes. The analysis was done to measure the student performance in Thermodynamic I which final grade was used as the tools. The models show that Test 1 and Test 2 plays major role in the student final grade. Meanwhile assignments and quizzes play as a booster to their performances. The artificial intelligent model can be used for further investigate of the subject performance with include more predictor such as age, CGPA, gender and etc.